Crush - Wolff, Tracy (Parker, CO : Entangled Teen, 2020)
Returning to Katmere Academy, the Circle is caught in a power play and the Vampire Court fights for leverage while Hudson and Jaxon vie to make themselves the most important person to Grace -- one with secrets that appeal to her mind and the other with the love that has captured her heart. Meanwhile they all face an unspeakable evil and possibly the ultimate sacrifice.
Keywords: Good and evil -- Fiction; Vampires -- Fiction; Teenagers -- Fiction; Boarding schools -- Fiction; Man-woman relationships -- Fiction; Romance fiction; Paranormal fiction